2018
DOI: 10.17707/agricultforest.64.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity, Acethylcolinesterase and Glutathione S-Transferase Effects of Halocnemum Strobilaceum Crude Extract Against Tribolium Castaneum

Abstract: Halocnemum stobilaceum (Chenopodiaceae) is one of many halophyte plants from Algerian Sahara. In this study, we investigate the phytochemical composition and the insecticidal activity of the crude ethanolic extract of this plant against adults of the red flour beetle Tribolium castaneum (Coleoptera: Tenebrionidae). Te effect of this extract on the detoxification enzyme Glutathione S-transferase (GST) and the neuroenzyme Acethylcolinesterase (AChE) was also investigated. The repellent effect was evaluated, at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…They contribute to the protection of cells from oxidative stress and chemical toxins by of electrophilic and lipophilic chemicals (Hayes andPulford 1995 andEnayati et al 2005). Several investigations have shown that when insects are exposed to pathogens, plant allelochemicals, and chemical pesticides, GST is activated (Qin et al 2011 andAcheuk et al 2018). This agrees with our findings, which showed that F. virgata exposed to the tested essential oils had high GST activity.…”
Section: Effects Of Essential Oils On Gst Activitymentioning
confidence: 99%
“…They contribute to the protection of cells from oxidative stress and chemical toxins by of electrophilic and lipophilic chemicals (Hayes andPulford 1995 andEnayati et al 2005). Several investigations have shown that when insects are exposed to pathogens, plant allelochemicals, and chemical pesticides, GST is activated (Qin et al 2011 andAcheuk et al 2018). This agrees with our findings, which showed that F. virgata exposed to the tested essential oils had high GST activity.…”
Section: Effects Of Essential Oils On Gst Activitymentioning
confidence: 99%
“…Its shoot fractions containing long-chain fatty acids, showed antibacterial activity against human pathogenic bacteria: Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Enterococcus faecalis and Salmonella typhimurium (2). The crude extract of Halocnemum strobilaceum showed insecticidal activity against red flour beetle Tribolium castaneum due to high content of saponins, gallic tannins, flavonoids, antocyans and alkaloids (3). The natural antioxidants from Halocnemum strobilaceum: flavonoid glycosides with quercetin, isorhamnetin, and icaritin moieties showed high activity against PC3, MCF-7 and A549 cancer cell lines (4).…”
Section: Introductionmentioning
confidence: 99%